SYSTEMATIC REVIEW: EFFECT TOLUENE ON DNA METHYLATION IN WORKERS - Alya Nabilah; Abdul Rohim Tualeka; Juliana Jalaludin; Suardi Zurimi (Faculty of Vocational Studies, Universitas Airlangga, 2026)
Background: Toluene is a chemical widely used in industry as a solvent or a mixture of other chemicals. Occupational toluene exposure can occur in painting, laboratories, car repair shops, and other industrial workplaces. Toluene exposure may cause epigenetic alterations and DNA methylation, which can lead to gene inactivation and may contribute to cancer development and other adverse health outcomes. Purpose: This systematic review aims to determine the effect of toluene on DNA methylation in workers. Review: The method of this research was a systematic review of the databases PubMed and Google Scholar. The inclusion criteria were studies involving workers exposed to toluene and employing experimental or observational studies published in English and within the last ten years. A total of five articles met the inclusion criteria and were included in the analysis. Result: Toluene exposure may cause epigenetic alterations and DNA methylation. The impact of toluene exposure on DNA methylation included gene inactivation, placental dysfunction, miscarriage, and increased risk of cancer. Conclusion: The findings of this systematic review highlight the importance of reducing occupational exposure to toluene. Industries should consider replacing toluene with more environmentally friendly alternatives, such as ethyl acetate, ethylcyclohexane, n-butyl acetate, and propylene glycol monomethyl ether, to minimize health risks to workers.